HUMAN RESOURCE MANAGEMENT (HRM) PRACTICES IN IMPROVING EMPLOYEE-BASED PERFORMANCE TOTAL QUALITY MANAGEMENT (TQM) - Vika Fransisca; Komarudin Komarudin (Proceedings of the 1st International Conference on Social Science (ICSS), 2023)
Human resources (HR) is an important thing for the organization because it is the main driver of activities carried out by the organization. In this HR company is a company employee, the performance of quality employees will determine the success or failure of a company. Thus, the need for human resource management (HRM) based on total quality management (TQM) to always improve employee performance. This study aims to determine human resource management (HRM) practices in improving employee performance based on total quality management (TQM). This research uses a descriptive method with a qualitative approach. Descriptive research is used to explain various events that occur. Meanwhile, a qualitative approach to explain events that occur in real and reasonable situations. The results showed that appropriate human resource management (HRM) practices can develop its assets, namely human resources. Various coaching and development in order to encourage human resources to have quality shown by employee performance. So that the practice of human resource management (HRM) in improving employee performance based on Total Quality Management (TQM) is a very important effort to maintain and improve employee performance so that the company can survive in increasingly fierce competition